Analisis Kontrapung Lagu Canon In D Major Karya Johann Christoph pachelbel - Yuniar, Farah Diva; Rachman, Abdul (Universitas Sultan Ageng Tirtayasa, 2024)
There are two approaches to counterpoint: free counterpoint and strict counterpoint. Free counterpoint is free in composing melodies, while strict counterpoint is done using species counterpoint. Each counterpoint species has rules in composing counterpoint melodies and cantus the firmus melodies. This research aims to describe strict counterpoint in the song 'Canon In D Major by Johann Christoph Pachelbel'. The research method used is qualitative research method, data is obtained by observation, documentation, interview, and document study, the data validity technique is done by data reduction stage, data presentation stage, and conclusion drawing and verification stage. The song Canon In D Major has a 4/4 beat with a total of 57 beats, and Adagio Sustenuto tempo. The song is a musical work in the form of a polyphonic canon. The song creation process uses strict counterpoint, namely, the first species, second species, third species, fourth species, fifth species.